Advantageous crystalline–amorphous phase boundary for enhanced electrochemical water oxidation. Issue 8 (28th May 2019) - Han, HyukSu; Choi, Heechae; Mhin, Sungwook; Hong, Yu-Rim; Kim, Kang Min; Kwon, Jiseok; Ali, Ghulam; Chung, Kyung Yoon; Je, Minyeong; Umh, Ha Nee; Lim, Dong-Ha; Davey, Kenneth; et al.
Abstract : Crystalline–amorphous phase boundary engineering can be an effective strategy to develop cost-effective and high-performance electrocatalysts for water splitting. Abstract : The development of cost-effective and high-performance electrocatalysts for water oxidation has attracted intense research interest. It was reported recently that the interface between the amorphous and crystalline phases plays a significant role in the electrocatalytic activity of transition metal compounds. It was reckoned therefore that an increase in the density of the crystalline–amorphous phase boundary would enhance the electrochemical water oxidation on the catalyst. In this work we develop a new and facile strategy for inducing high density crystalline–amorphous phase boundaries via selective fluorination surface doping. This resulted in excellent characteristics of the engineered material for electrochemical water splitting. An initial computational simulation is carried out to design the crystalline–amorphous phase boundary material and an experimental verification follows for demonstration and optimization of the impact of surface doping. We conclude that the engineering of the interface using this facile and cost-effective strategy maximizes the crystalline and amorphous phases of metal–metalloids, which can be used to fabricate low-cost and efficient electrocatalysts for water oxidation.